A Brief Review of Forced Repetitions for the Promotion of Muscular Hypertrophy. Issue 5 (October 2015) - Hackett, Daniel A.; Amirthalingam, Theban
Abstract : ABSTRACT: FOR ADVANCED TRAINERS TARGETING MUSCULAR HYPERTROPHY, IT IS RECOMMENDED THAT THE MAJORITY OF TRAINING BE DEVOTED TO 6–12 REPETITIONS AT MODERATE LOADING (70–85% 1 REPETITION MAXIMUM) FOR MULTIPLE SETS, PERFORMED TO OR CLOSE TO MOMENTARY MUSCULAR FAILURE (MMF). AN ADVANCED TRAINING TECHNIQUE THAT CAN BE USED AFTER REACHING MMF IS FORCED REPETITIONS (FR). HOWEVER, THERE IS LITTLE SCIENTIFIC EVIDENCE TO CONFIRM ANY POSITIVE BENEFITS ATTRIBUTED TO THE USE OF FR. THIS REVIEW DISCUSSES THE RELEVANT LITERATURE REGARDING THE EFFICACY OF FR FOR THE PROMOTION OF MUSCULAR HYPERTROPHY. RECOMMENDATIONS ARE DISCUSSED FOR TRAINERS SURROUNDING THE PRESCRIPTION OF FR.